DEMYSTIFICATION OF BOGOR AS A CITY WITHOUT WORRIES - Permana, Tenu; Yudhistira, Reza; Trisari, Agatha; Riandi, Muhammad Fadhilah (Jurnal Salaka : Jurnal Bahasa, Sastra, dan Budaya Indonesia, 2025)
This study analyzes the history and sociocultural background that gave rise to the mystification of Bogor (Buitenzorg) as a city without worry, and then demystifies and deconstructs it. This research aims to deconstruct the mystification of Bogor as a city without fear by examining the history of collective action that led to resistance in the Bogor area. This study also describes the sociological factors and changes in natural conditions that have changed from the colonial period to the present day. This research employs a qualitative descriptive approach and draws on deconstruction theory to reconstruct the history that shapes the identity of the Bogoran. The results of this study show that Bogor, which is famous for being a city without worry, is a result of colonial power conditions. That inherent and maintained identity is the result of knowledge imposed by power. The deconstruction carried out in this study ultimately led to the dismantling of meaning, revealing that Bogor had a more complex history than just being a resting place. There is also a stage for various forms of collective action of resistance from the colonial era, independence, to post-independence.